Fluid flow measurement a practical guide to accurate flow measurement - Upp, E. L. 1927-2007; LaNasa, Paul J., 1941- (Butterworth-Heinemann, 2014)
There is a tendency to make flow measurement a highly theoretical and technical subject but what most influences quality measurement is the practical application of meters, metering principles, and metering equipment and the use of quality equipment that can continue to function through the years with proper maintenance have the most influence in obtaining quality measurement. This guide provides a review of basic laws and principles, an overview of physical characteristics and behavior of gases and liquids, and a look at the dynamics of flow. The authors examine applications of specific meters, readout and related devices, and proving systems. Practical guidelines for the meter in use, condition of the fluid, details of the entire metering system, installation and operation, and the timing and quality of maintenance are also included. This book is dedicated to condensing and sharing the authors' extensive experience in solving flow measurement problems with design engineers, operating personnel (from top supervisors to the newest testers), academically-based engineers, engineers of the manufacturers of flow meter equipment, worldwide practitioners, theorists, and people just getting into the business.
Previous edition: Boston, Mass.; Oxford: Gulf, 2002.
Keywords: Fluid dynamic measurements.; Flow meters.; elektronické knihy; electronic books